Exploring the Body
XXI, 246 p.
Keywords: This volume explores diverse ways of researching and theorizing the body. It draws together a range of empirical work on different themes, each taking the body and its study as its central problematic. It creatively combines contributions on disability, illness, scars, sleep, complementary medicine, running, as well as the lifecourse themes of childhood, youth and death. The different approaches to researching the body examined through these contributions include autobiography, case-studies, interviews and participant observation.